2017
DOI: 10.3390/md15070199
|View full text |Cite
|
Sign up to set email alerts
|

Poecillastrosides, Steroidal Saponins from the Mediterranean Deep-Sea Sponge Poecillastra compressa (Bowerbank, 1866)

Abstract: The first chemical investigation of the Mediterranean deep-sea sponge Poecillastra compressa (Bowerbank, 1866) led to the identification of seven new steroidal saponins named poecillastrosides A–G (1–7). All saponins feature an oxidized methyl at C-18 into a primary alcohol or a carboxylic acid. While poecillastrosides A–D (1–4) all contain an exo double bond at C-24 of the side-chain and two osidic residues connected at O-2′, poecillastrosides E–G (5–7) are characterized by a cyclopropane on the side-chain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…The new compounds showed potent growth inhibitory activity against the human leukemia cell line K562. This finding, combined with those regarding the previously reported steroidal glycosides with potent activities against various cancer cell lines [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], would provide new insights into the structure-activity relationships of cytotoxic sulfated steroidal glycosides.…”
Section: Discussionsupporting
confidence: 55%
“…The new compounds showed potent growth inhibitory activity against the human leukemia cell line K562. This finding, combined with those regarding the previously reported steroidal glycosides with potent activities against various cancer cell lines [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], would provide new insights into the structure-activity relationships of cytotoxic sulfated steroidal glycosides.…”
Section: Discussionsupporting
confidence: 55%
“…Saponins form an important class of natural products first discovered in higher plants [39]. In the marine environment, saponins are secondary metabolites mainly produced by echinoderms [40], although saponins have also been isolated from other marine invertebrates, such as octocorals or sponges [41,42,43]. Numerous studies have been conducted on these compounds that are characterized by a large chemical diversity and a wide variety of pharmacological activities [7,39,44,45,46,47,48].…”
Section: Saponin Occurrence and Diversity In Echinodermsmentioning
confidence: 99%
“…In another study by Fouad et al [29], it was observed that saponins obtained from marine sponge crude extracts only showed bioactivity against C. albicans and not MRSA. Calabro et al [30] further reported the same ndings as their marine sponge Poecillastra compressa from the Mediterranean Deep-Sea contained saponins that only showed antifungal properties when tested against A. fumigatus. In our study, both antibacterial and antifungal activity was observed in the ethyl acetate crude extract, which contained saponins.…”
Section: Discussionmentioning
confidence: 74%